Impact of maternal sociodemographic characteristics on infant and child nutrition and growth: a cross-sectional observational study - Mete, Basundhara; Randev, Shivani; Guglani, Vishal (International Journal of Contemporary Pediatrics, 2025)
Background: A high prevalence of malnutrition in infants in India may be associated with socio-demographic characteristics of mother. We wanted to find out the association between maternal socio-demographic factors, dietary diversity and growth in 12 to 24 months children. Methods: We enrolled 12 to 24 months children over 11 months in a tertiary care centre in North India, from outpatient and inpatient wards in an observational, cross-sectional study. Maternal education, occupation and socio-economic status were noted. Dietary history was recorded to determine Minimum Meal Frequency (MMF) and Minimum Dietary Diversity (MDD) as per WHO guidelines. Child’s weight, length/height, mid upper-arm circumference (MUAC) and occipitofrontal circumference were recorded. Outcomes were proportion of underweight, stunted, wasted and severe acute malnutrition (SAM defined as MUAC <11.5 cm) in various dietary adequacy groups and as per maternal socio-demographics. Results: Authors enrolled 246 children and mean (SD) age at assessment was 17.6(4.2). Mothers of 210 (85.4%) were unemployed, 73(29.7%) either uneducated or educated less than 10th and 31(12.6%) completed post-graduation. Complementary feeding was initiated between 6 months to 1year age in 208(84.2%) children. MMF was met in 169 (68.7%) and MDD in 74(30%). We found 79(32%) children were underweight, 51(20.7%) wasted, 83(33.7%) stunted and 20 (8.7%) SAM. Nearly 72% of unemployed mothers failed to provide MDD versus 55% (p=0.042) employed mothers. MDD increased with increasing education of mother(p=0.002). Children of less educated mothers had significantly higher underweight (p=0.029) and stunting (p=0.006). Conclusion: Dietary diversity and growth are significantly affected by maternal sociodemographic characteristics in 12-24 months children.